The reliable predictors of severe weight loss during the radiotherapy of Head and Neck Cancer - Vahideh Nazari; Abdolazim Sedighi Pashaki; Elyas Hasanzadeh (Cancer Treatment and Research Communications, 2021)
Side effects of severe weight loss during radiation therapy and its definitive risk factors are the significant complexities of cancer treatment. This study aimed to identify the reliable predictors of severe weight loss during three-dimensional conformal radiation therapy (3D-CRT) in head and neck cancer patients. Weight changes during radiotherapy were investigated on 87 patients. Tumor site, T-stage, BMI, age, smoking, treatment modality, and prior surgery were considered as effective factors. During the 3D-CRT, 78.7% of patients experienced weight loss (p<0.001). The risk of weight loss was higher in patients with cancer in the larynx and oral cavity. Severe weight loss (≥5% during the radiation course) was observed in 47.8% of patients. There was the highest risk of severe weight loss in patients undergoing chemoradiation therapy with previous surgical resection (83.3%). The incidence of severe weight loss in normal-weight patients compared to overweight patients was significant. Severe weight loss was more common at higher doses and in younger patients. BMI regardless of body composition is not a credible predictor. Advanced tumor stage and combined treatment modality in head and neck cancer patients which result in synergizing of treatment toxicities, can be used as the reliable risk factors of severe weight loss during radiotherapy.